pH Metric Studies on Some Binary Complexes of Dysprosium(III) and Ytterbium(III) with Ligands Containing N,N-Donor Atoms - PATEL, K.P.; PABREJA, D.S. (Asian Journal of Chemistry, 2010)
The present paper describe pH-metric study on formation constant of binary complexes of dysprosium [Dy(III)] and ytterbium [Yb(III)] with amines has been carried out at constant temperature 30 ± 0.1 ºC. The ionic strength μ = 0.2 M dm-3 was held constant was held constant using NaClO4 as an electrolyte. Various factors influencing the formation and stabilities of binary complexes have been discussed.